Interactive effects of climate and nutrient enrichment on patterns of herbivory by different feeding guilds in mangrove forests. Issue 11 (28th September 2017) - Feller, Ilka C.; Ball, Marilyn C.; Ellis, Joanne I.; Lovelock, Catherine E.; Reef, Ruth
Abstract: Aim: Global warming and eutrophication are major threats to coastal environments worldwide. As a result of differences between temperate and tropical ecosystems in nutrient availability, nitrogen (N):phosphorus (P) coupling and carbon retention, primary productivity and biotic interactions in the tropics are predicted to have stronger responses to increased nutrients than in temperate ecosystems. Habitats that occur across broad climatic ranges, such as mangrove forests, provide an opportunity to test this hypothesis by investigating the responses of herbivores to nutrient enrichment in temperate versus tropical latitudes on the same species. Location: Australia and New Zealand. Time period: Fertilization experiments were established at Port Douglas and Cape Cleveland in October 2000; Batemans Bay and Waikopua in August 2001; Whangapoua in January 2003; Tinchi Tamba in September 2005; and Garalia in October 2007. Herbivory was measured in 2009. Major taxa studied: Insect leaf miners; insect and fungal leaf gallers. Methods: We used seven fertilization experiments in Australia and New Zealand across 20° of latitude to determine how increased nutrients affected herbivory and diversity of leaf miners and gallers of the mangrove Avicennia marina . Individual trees were fertilized annually with one of three treatments (Control, +N, +P); herbivory was measured in 2009. Results: Fertilization did not significantly affect herbivory or herbivore diversity. Leaf N:P, latitude and rainfall contributed significantly to herbivory, accounting for > 56% of the variation. Latitude, temperature, %P and salinity differentiated herbivory by feeding guild in the tropical versus subtropical and temperate latitudes. The effect of N fertilization on folivory differed across climatic regions; relative to Control trees, N‐fertilized trees in temperate areas had greater folivory than in tropical and subtropical latitudes. Species richness for leaf miners and gallers was correlated with latitude, with more species in subtropical and tropical latitudes than in temperate latitudes. The abundance of galls and mines differed by location, but differences were not correlated with latitude. Main conclusions: Results indicate that latitude and nutrients may have had an interactive effect on herbivory and herbivore diversity of A. marina . However, the strength of the interactions varied by climatic region and was not the same for all groups of herbivores.